OPPORTUNITIES AND CHALLENGES FOR ISLAMIC FINTECH IN THE GLOBAL MARKET - Ma'rifah, Eva Fauziah; Mohammad Ridwan, M.Pd., (P3M - STAI Kuningan, 2024)
Sharia fintech has become a significant phenomenon in facing the transformation of the global financial industry, presenting unique opportunities and challenges in the global market. These opportunities include wider financial access for Muslim communities, sharia product innovation that can meet growing market needs, and increased efficiency in financial services. However, along with these opportunities, Sharia Fintech also faces challenges, including complexity in complying with sharia, public perception of technology-based financial products, and varying regulations in various countries.